Anode-free post-Li metal batteries - Petersen, Deik (2024)
Anode-free metal batteries (AFMBs) are a new architecture of battery technology that relies solely oncurrent collectors (CCs) at the anode side, eliminating the need for traditional metal anodes. Thisapproach can pave the way for higher energy densities, lower manufacturing costs, and lowerenvironmental footprints associated with metal batteries. This comprehensive review provides an indepthexploration of AFMB technology, extending its scope beyond lithium and into a broader range ofmetals (sodium Na, potassium K, magnesium Mg, zinc Zn and aluminum Al). The concept of ‘‘metalphilicity’’is discussed, which plays a pivotal role in understanding and controlling metal plating behaviorwithin AFMBs, and also computational studies that employ first-principles calculations. This novel notionoffers valuable insights into the interactions between metals and CC surfaces, which are essential fordesigning efficient battery systems. Moreover, the review explores various materials and experimentalmethods to enhance metal plating efficiency while mitigating issues such as dendrite formation throughthe realm of surface modifications and coatings on CCs. By providing a deeper understanding ofstrategies for optimizing anode-free post-Li metal battery technologies, this review aims to contribute todeveloping more efficient, sustainable, and cost-effective energy storage for the near future.